Systemic Functional Linguistics to Preserve Interpersonal and Ideational Meaning in English-Indonesian Translation - Tanzir Masykar; Febri Nurrahmi; Tabsyir Masykar (UNIB Press, 2023)
Systemic functional linguistic (SFL) is a language theory that emphasize social function of a language in realizing meaning. Traditional ways of translating Indonesian text has relied heavily on generative grammar or grammar translation method. Using this method, the grammatical function of an utterance may be well preserved yet at the stake of meaning shift. Register (field, mode and tenor) is an important feature in SFL that may help translators preserving ideational meaning and tenor from the source language to target language. English sentences on specific scenarios are translated into Indonesian and vice versa using grammar translation method and systemic functional linguistic. The results are compared to observe translation shift, ideational, interpersonal and textual meaning. The findings showed that grammar translation method fail to transfer the ideational meaning into Indonesian despite preserving experiential features are intact. This does not happen in systemic functional linguistic approach since the approach requires preserving the functional meaning of a sentence instead of the grammar. The grammar categories may change using SFL but the functional meaning is well preserved. Emphasizing functional meaning instead of grammatical function enable translators to deliver equal meaning in Indonesian. While tenor is not a problem in the translation of Indonesian to English, translators need to carefully consider field, mode and tenor when translation texts from English to Indonesian.